Improving the mechanical characteristics of environmentally friendly concrete using fly ash and brick powder as partial sand replacements - Filali, Saloua; Nasser, Abdelkader; Azougay, Abdellah (Građevinski materijali i konstrukcije, 2024)
Infrastructure and urbanization drive the demand for concrete, which puts pressure on natural resources and jeopardizes the ecosystem. Incorporating recycled materials into concrete can fulfill this demand without sacrificing quality. This study examines the mechanical properties of sustainable concrete, employing fly ash (FA) and brick powder as substitutes for sand in fine aggregates. We evaluated rebound hammer strength, ultrasonic pulse velocity (UPV), workability, compressive strength, and split tensile strength using both destructive and non-destructive assessment methods, comparing them to conventional concrete. Concrete mixtures were developed by substituting 10% of natural sand with brick powder and gradually replacing the remaining sand with fly ash at 10% to 50%. The results clearly show that the best mix of 10% brick powder and 40% fly ash increases compressive strength by 64.81%, split tensile strength by 17.78%, and workability by 48%. The identical mixture yields a notable enhancement in ultrasonic pulse velocity (UPV) of 33.15%, achieving a velocity of 4.9 km/s, and a 32.05% increase in rebound number, resulting in a rebound index of 44.92. A regression analysis indicated a significant correlation among compressive strength, UPV, and rebound index. The combination of 10% brick powder and 40% fly ash results in enhanced mechanical performance, reduced costs, and supports sustainable construction practices.